Literatur Review : Pengaruh Tradisi Mengunyah Sirih Terhadap Kesehatan Gigi - Aditya, Ronal Surya; Alifatunnisa, Alifatunnisa; Elvarelta, Chysaura Malva; Adhitama, Felicia Dewati Elit; Khusna, Nasya Zilza; Betay, Oskar; Andayani, Sari Dewi (Universitas Negeri Malang, 2024)
The habit of nginang (chewing betel), which has been practiced for generations in various tribes in Indonesia, has various health benefits. The belief that chewing betel nut can prevent oral diseases and treat toothache and bad breath may be deeply ingrained among its users. The purpose of this study was to explore an in-depth understanding of the phenomena relevant to this research topic. This study used the literature review.method by taking ten different article titles with the criteria of selecting literature sources covering the time span of publication in the last ten years in order to include current and relevant information. Literature sources were obtained through searching using the search engine